A comunidade de microliquens crostosos sofre alteração ao longo de gradientes ambientais na caatinga? - Rodrigues, Luciana Calado (2012)
Lichens are a quite diverse group of organisms and important components of the diversity of tropical forests since they act as pioneer organisms in the colonization of terrestrial environments and play various roles in ecosystems. However, studies on the ecology of lichens only in areas of Caatinga are still lacking. This study, which was held in a conservation area of caatinga in the State of Sergipe, is the first to investigate the composition of lichen species on this site. Thus, the dissertation is divided into two chapters: the first deals with the survey of the lichenized mycota at the Natural Monument Grota do Angico and discusses the occurrence of new records of lichens. A total of 2210 specimens of lichens was analyzed and 65 taxa could be identified, distributed in 14 families and 29 genera. As a result, 11 species are new records of corticicolous crostose lichens to Brazil, 09 to the Northeast Region and 15 to the state of Sergipe. The second chapter deals with the investigation of three hypotheses: (1) that there is positive relationship between trees species richness and the lichens species richness, (2) there is a positive relationship between the abundance of trees and abundance of lichens, and (3) that canopy openess, DBH, temperature, pH and moisture positively affect the diversity and composition of lichens. Of the variables analyzed, only canopy openness and DBH were associated with lichens species richness. The results suggest that there is a positive relationship between canopy openness and abundance of lichens.